Healing in the Joys of Creation: Mystery as Teacher and Medicine - Elke, Ramona (Journal of the Canadian Association for Curriculum Studies, 2025)
This work explores the importance of including, in the curriculum, Indigenous teachings regarding making, creating, healing and mystery. Found in the teachings of many Indigenous peoples, mystery, or (not) knowing, is vital to coming to know how to be human in a good way and so it must be centred and honoured in our walk through this world. Drawing on what I have learned from my many life teachers, I humbly offer the suggestion that mystery is vital in our route to the healing of ourselves and our world. In this work of Indigenous métissage, offering up my own experiences, I narrate how, through making and creating practices such as beading, drumming, weaving, poetry and life writing, I, and the youth with whom I teach and learn, have been invited into spaces of (not) knowing, where we have been made available to joy and healing. In this essay, I bring forward poems, stories from my teaching and making life, and images of my beading and painting, as an offering of one path of surrendering to mystery in the search for mino bimaadiziwin—living in a good way for the good of All My Relations.